Interaction of microplastics and terrestrial and aquatic insects (bioaccumulation, degradation, ecotoxicological effects) - Lee, Mark; Simakova, Anastasia V.; Babkina, Irina B.; Bagirov, Ruslan T-o; Frank, Yuliya A. (Acta biologica sibirica)
World production of convenient and durable materials made of synthetic plastics during the last 70 years caused the dispersal of microplastic particles in the environment. Microplastic pollution is the focus of interest worldwide due to its global distribution and adverse effects on living organisms. The largest number of studies addressing this issue explored the aquatic environment, yet terrestrial ecosystems also suffer from microplastic pollution. Insects are crucial for most terrestrial ecosystems. Few can compete with them in biomass productivity and species diversity, which makes them targets for studying the toxic bioaccumulation. This review article presents a systematic analysis of data on bioaccumulation, degradation of microplastics by aquatic and terrestrial entomofauna, and its ecotoxicological effects.